2015
DOI: 10.1186/s13717-015-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cu (II) ions using sodium salt of 4-phenylsemicarbazone 1,2-naphthoquinone-4-sulfonic acid in natural and industrial environments

Abstract: Introduction: The copper content in natural waters usually range from 0.2 to 30 μg/L. The higher concentrations are habitually found in industrial effluents and other contaminated waters. Methods: This work develops the spectrophotometric method of determination of copper (II) microgram amounts with a new reagent -sodium salt of 4-phenylsemicarbazone 1,2-naphthoquinone-4-sulfonic acid (L), used as a ligand for a new coordination compound of copper (II). The complex formation is accompanied by color change, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The common methods for the detection of Cu(II), as for Cr(VI), include liquid chromatography, electrochemical detection, spectrophotometry, solid-phase extraction coupled with atomic absorption spectroscopy, potentiometric techniques, X-ray fluorescence, atomic emission spectroscopy, and inductively coupled plasma mass spectrometry [104,105]. According to Ramanjaneyulu et al [106,107], the existing reagents for the photometric determination of Cu permit the detection of 0.025-30 μg/mL Cu. For instance, the diethyldithiocarbamate reagent is considered one of the most frequently used reagents for Cu(II) determination with a LOD of 0.1 μg/L.…”
Section: Cu Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The common methods for the detection of Cu(II), as for Cr(VI), include liquid chromatography, electrochemical detection, spectrophotometry, solid-phase extraction coupled with atomic absorption spectroscopy, potentiometric techniques, X-ray fluorescence, atomic emission spectroscopy, and inductively coupled plasma mass spectrometry [104,105]. According to Ramanjaneyulu et al [106,107], the existing reagents for the photometric determination of Cu permit the detection of 0.025-30 μg/mL Cu. For instance, the diethyldithiocarbamate reagent is considered one of the most frequently used reagents for Cu(II) determination with a LOD of 0.1 μg/L.…”
Section: Cu Detection Methodsmentioning
confidence: 99%
“…For instance, the diethyldithiocarbamate reagent is considered one of the most frequently used reagents for Cu(II) determination with a LOD of 0.1 μg/L. Zagurskaya et al [107] developed a spectrophotometric method of determination of Cu(II) with a ligand for a new coordination compound, the sodium salt of 4-phenylsemicarbazone 1,2-naphthoquinone-4-sulfonic acid (L). The formation of this new complex is accompanied by a color change and LOD of 0.012 mg/L.…”
Section: Cu Detection Methodsmentioning
confidence: 99%
“…The chemical industry is highly diverse and a large number of chemical products are used and produced in manufacturing processes. It has resulted in the formation of wastewater contaminated with organic and inorganic substances of very different composition and volume [1][2]. Hence, heavy metals released by industrial activities are increasingly being found in freshwater to affect the quality of water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Cu(II) is the third most abundant transition-metal ion in the human body and is essential for the biochemical and physiological functions [4]. Its deficiency and excess lead to malfunction of the liver, heart diseases, neurological disorders, and deterioration of connective and bone tissues [1].…”
Section: Introductionmentioning
confidence: 99%
“…The multiple applications in industry, agriculture, medicine, and technology widely use chemical products to result in a wide distribution of chemicals in the environment. These results raise concerns over potential effects of chemicals on human health and the environment [10][11][12]. Therefore, the detection of heavy metals in aqueous environments has attracted wide attention in recent years.…”
Section: Introductionmentioning
confidence: 99%